Study Of Plant Regeneration Potential In Tropical Moist Deciduous Forest In Northern India - Mishra, Ashish K; Bajpai, Omesh; Sahu, Nayan; Kumar, Anoop; Behera, Soumit K; Mishra, RM; Chaudhary, Lal Babu (International Journal of Environment, 2013)
Regeneration patterns of species population can address climate change by adaptive evolution or by migrating association to survive in their favorable climate and finally decided to particular forest future. In this paper we examined the status of regeneration potential of tree species in tropical moist deciduous forest at Katerniaghat Wildlife Sanctuary, Northern India. To investigate tree, sapling and seedling population distribution, we examine regeneration status in 145 random plots in study area. Total 74 plant species of 60 genera belonging to 32 families out of which 71 species of trees, 56 of seedlings and 60 of saplings were found in the forest. On the basis of importance value index Mallotus philippensis, Tectona grandis, Shorea robusta, Syzygium cumini and Bombax ceiba have been found as dominant species in the study area. As far as the regeneration status is concerned, the maximum tree species (64%) have been found in good regeneration category. Significant variations in species richness and population density, between three life form (i. e. tree, sapling and seedling) have been found. In which only three new tree species Prosopis juliflora, Psidium guajava and Morus alba were added in sapling and seedling stage. It is major ecological concern that about 19 % economically important plant species like Madhuca longifolia, Terminalia elliptica, Buchanania cochinchinensis, some Ficus species etc. have been found in poor regeneration phage, whereas about 7% species found in no regeneration categories. International Journal of Environment, Volume-2, Issue-1, Sep-Nov 2013, Pages 153-163 DOI: http://dx.doi.org/10.3126/ije.v2i1.9218